2011
DOI: 10.3389/fpsyg.2011.00344
|View full text |Cite
|
Sign up to set email alerts
|

To Take Risk is to Face Loss: A Tonic Pupillometry Study

Abstract: The construct of risk taking is studied through the prism of the relation between tonic arousal and risk taking behavior. Several theories have proposed that high aroused individuals tend to exhibit risk aversion. We posit that this arousal–behavior association is activated much more strongly in risks with losses, as losses increase arousal and trigger relevant traits associated with the sensitivity to risk. In three studies we examined risk taking in experience-based decision tasks, with either token losses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 62 publications
4
16
0
1
Order By: Relevance
“…Tonic mode is analogous to pupil measurements that are collected continuously over a longer period of time (most of the time as a baseline measurement). For adults, tonic pupil size or baseline pupil size has been measured to study intelligence (Tsukahara, Harrison, & Engle, 2016), risk-taking behavior (Yechiam & Telpaz, 2011), motivation (Wykowska, Anderl, Schubö, & Hommel, 2013) and control state (Gilzenrat, Nieuwenhuis, Jepma, & Cohen, 2010), but overall, is measured less than phasic pupil size (Laeng et al, 2012). For younger populations, tonic pupil size has been used to investigate autistic spectrum disorder (Blaser, Eglington, Carter, & Kaldy, 2014), social cognition (Anderson, Colombo, & Jill Shaddy, 2006), emotion (Geangu, Hauf, Bhardwaj, & Bentz, 2011), and motivation (Hepach, Vaish, & Tomasello, 2012;Hepach, Vaish, & Tomasello, 2013).…”
Section: Overview Of Pupillometrymentioning
confidence: 99%
“…Tonic mode is analogous to pupil measurements that are collected continuously over a longer period of time (most of the time as a baseline measurement). For adults, tonic pupil size or baseline pupil size has been measured to study intelligence (Tsukahara, Harrison, & Engle, 2016), risk-taking behavior (Yechiam & Telpaz, 2011), motivation (Wykowska, Anderl, Schubö, & Hommel, 2013) and control state (Gilzenrat, Nieuwenhuis, Jepma, & Cohen, 2010), but overall, is measured less than phasic pupil size (Laeng et al, 2012). For younger populations, tonic pupil size has been used to investigate autistic spectrum disorder (Blaser, Eglington, Carter, & Kaldy, 2014), social cognition (Anderson, Colombo, & Jill Shaddy, 2006), emotion (Geangu, Hauf, Bhardwaj, & Bentz, 2011), and motivation (Hepach, Vaish, & Tomasello, 2012;Hepach, Vaish, & Tomasello, 2013).…”
Section: Overview Of Pupillometrymentioning
confidence: 99%
“…In the decision making domain, a recent line of research has been trying to shed light on the boundaries of some well-known phenomena documented in previous literature. This is the case of the recent discussions about the robustness and generality of loss aversion provided by, for example, Ert and Erev ( 2008 , 2013 ) and Yechiam and Hochman ( 2014 ) 7 ; the conditions for underweighting of rare events (e.g., Rakow et al, 2008 ); or the construct of risk taking by Yechiam and Telpaz ( 2011 , 2013 ).…”
Section: Apparently Inconsistent Biasesmentioning
confidence: 99%
“…Consistent with behavioral evidence for loss aversion, recent neuroeconomics findings have shown that losses elicit greater event-related brain potentials (Gehring & Willoughby, 2002), skin conductance responses (Sokol-Hessner et al, 2009), increased heart rate and pupil dilation (Hochman & Yechiam, 2011), and activation in several brain regions (ventral striatum, amygdala, medial prefrontal cortex; Rutledge & Glimcher, 2009) than equivalent gains. However, some studies have discovered some situations where behavioral loss aversion does not appear (Hochman & Yechiam, 2011;Koritzky & Yechiam, 2010;Novemsky & Kahneman, 2005;Yechiam & Ert, 2011; for a review, see Yechiam & Hochman, 2013), although other studies have found evidence for increased arousal following losses, relative to gains, even when there is no evidence for behavioral loss aversion (Gehring & Willoughby, 2002;Hochman, Glöckner, & Yechiam, 2010;Hochman & Yechiam, 2011;Yechiam & Telpaz, 2011). Together, although recent work suggests that behavioral loss aversion is not universal, there is an extensive body of work that suggests a distinct role for losses compared with gains.…”
Section: Introductionmentioning
confidence: 99%